Helminths in house lizards (Reptilia: Gekkonidae) - Saehoong P. (2014)
A survey of helminths in house lizards captured in Amphoe Maung, Chiang Mai Prouince revealed that the prevalence of helminthic infections in Cosymbotus platyurus was 94.4% and in Hemidactylus frenatus was 100%. Six species of helminths were found from C. platyurus: two species of trematodes, Posterochigenes sp (16.7%), Paradistomoides gregarium (41.1%); one species of cestode, Oochoristic sp (3.3%); two types of acanthocephalan cystacant, Type I (4.4%), type II (3.3%); and one species of nematode, Pharyngodon sp (83.3%). The cystacant Type II was not found in H. frenatus lizard, but the other five worms were found with higher prevalence. Pharyngodon was the common species in both lizards with the highest intensity range. So far, these worms have not been reported in human beings.